Native universe voices of Indian America - McMaster, Gerald 1953-; Trafzer, Clifford E.; National Geographic (Washington, D.C. National Museum of the American Indian, Smithsonian Institution, 2004)
Native American scholars, writers, and leaders examine the art and cultures of Indian peoples from the Arctic to Patagonia and from ancient times to the twenty-first century.
Defining past and future / W. Richard West, Jr. -- A new journey / Gerald McMaster, Clifford E. Trafzer -- Our universes : traditional knowledge shapes our world -- Ceremony and ritual : life in motion / John C. Mohawk -- Heart of heaven, heart of earth : the Maya worldview / Victor Montejo -- Keeping the original instructions / Gabrielle Tayac -- Portfolio : our universes -- Carriers of the dream wheel : poem / N. Scott Momaday -- Sacred Feline / José Montaño -- Our peoples : giving voice to our histories -- Promises made, promises broken / Vine Deloria, Jr. -- Indian education, American education / Brenda J. Child -- Season of struggle / Paul Chaat Smith -- Alcatraz Proclamation -- Portfolio : our peoples -- This land belongs to us / Tatanka Yotanka (Sitting Bull) -- Our lives : contemporary life and identities -- Coming home / James Pepper Henry -- A new path for the people / Wilma Mankiller -- Deer dance / Linda Hogan -- The radiant curve: Navajo ceremony in contemporary life / Luci Tapahonso -- Powwow / George P. Horse Capture -- Portfolio : our lives -- Smoke signals : excerpt / Sherman Alexie -- Dear John Wayne : poem / Louise Erdrich.
"[Published by] National Museum of the American Indian, Smithsonian Institution in association with National Geographic."--Title page
Includes bibliographical references (pages 308-312) and index.
Keywords: Indians -- History; Indian cosmology; Indians -- Material culture; Indians -- Social life and customs; America -- Antiquities